RANCANG BANGUN DIGITAL SIGNAGE SEBAGAI PAPAN INFORMASI KEHADIRAN ASISTEN LABORATORIUM BERBASIS RFID - Rizqina Rihadatul 'Aisy; Nifty Fath; Eka Purwa Laksana (MAESTRO, 2023)
The laboratory has information that must be updated frequently to provide students with information regarding the presence of laboratory assistants. Therefore, in this study, digital signage will be used as an information medium that can display laboratory assistant presence data in real-time. Through digital signage, laboratory assistant presence information can be displayed digitally and accurately. The initial step of the program is to initiate the database. After the E-KTP is attached to the RFID, the database will check whether the identity on the card is recognized or not. If the card is registered on the attendance form, it will be displayed on digital signage. Based on the test results, the use of digital signage as an information board based on RFID as a method of identifying the presence of laboratory assistants has given good results. This system can display real-time and accurate attendance information through digital signage. In addition to testing the duration of the RFID reading when exposed to obstacles in the form of plywood and acrylic and when not exposed to obstacles, it shows variations in reading duration depending on the surrounding environment of the RFID reader. Furthermore, Quality of Service (QoS) testing was carried out, which showed very good results according to TIPHON standards. The test results show the lowest delay in the morning using a tethering network with a value of 11 ms and the highest throughput in the morning using a tethering network with a value of 736.649 bits/s. Packet loss and jitter are 0 each time.